The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1590/s0104-59702007000400013
|View full text |Cite
|
Sign up to set email alerts
|

Tributo a Manoel da Gama Lobo (1835-1883), pioneiro na epidemiologia da deficiência de vitamina A no Brasil

Abstract: Analisa a contribuição do médico paraense Manoel da Gama Lobo à história da epidemiologia da deficiência de vitamina A no Brasil. Tem como foco central de investigação a obra "Da oftalmia brasiliana", publicada originalmente em 1865. A trajetória acadêmica de Gama Lobo, particularmente essa obra, nos leva a identificar estreitos laços de comunhão entre o cientista e o grupo de médicos da Escola de Medicina Tropicalista Baiana. Embora não se possa creditar a Gama Lobo uma possível filiação às idéias do moviment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…One of these studies was conducted by a physician from Pará called Manuel da Gama Lobo (1835-1883), considered the pioneer of the epidemiology of vitamin A deficiency in Brazil 30 :…”
Section: Poor Man's Food: Food In Shanties Tenements and Shacksmentioning
confidence: 99%
“…One of these studies was conducted by a physician from Pará called Manuel da Gama Lobo (1835-1883), considered the pioneer of the epidemiology of vitamin A deficiency in Brazil 30 :…”
Section: Poor Man's Food: Food In Shanties Tenements and Shacksmentioning
confidence: 99%
“…At the end of his report, Dr. Gama Lobo called the attention of legislators to the need for laws aimed at preventing the sequence of problems he outlined. His paper was published in Portuguese and in German but is relatively unknown to the majority of the medical community, although it is now freely available online (11,12) . Recent epidemiologic data from Brazil in a study population of 3,499 children aged between 6 and 59 months and 5,698 women aged between 15 and 49 years revealed that hypovitaminosis A is present in all five regions of Brazil with a prevalence of 17.4% and 12.3% among children and women, respectively (13) .…”
Section: Introductionmentioning
confidence: 99%